Spacetimematter and quantum relations of affective e-motions - Jithya Merin Paul; Manali Karmakar (MethodsX)
This article has a double aim: it contributes to a new methodology of affect studies using an interdisciplinary approach by merging quantum field theory and new material readings of affect theory. Secondly, it aims to bridge the gap in affect studies by offering a quantum affective approach to understand the complex entanglements of multiple emotions that is beyond any form of codification. Until now, there have been complex negotiations between new affect theorists and neuroscience theorists to deconstruct/ structure emotions respectively. Evolving from Barad's concepts like agential realism and apparatus, the paper aims to bring out analogisms with e-motions and affect by combining concepts like quantum phenomena and dis/continuities to provide a new dimension in the understanding of affective matters through a quantum-affective approach. • To provide a new dimension to affect studies by conceptualizing affective matter as entangled phenomena characterized by dis/continuities, thereby enriching our understanding of the complexities of emotions beyond traditional categorizations. • To give a comprehensive method of understanding affect theory (which claims the very effort to explain it, itself is elusive and goes beyond any form of codification) through the concept of quantum relativity. • By applying quantum field theory to affect theory, the study not only enhances our idea of the complex nature of emotions but also offers a novel approach to analyse these emotions through concepts such as quantum phenomena, and quantum discontinuities. • The proposed quantum-affective approach emerges from the foundation laid by Karan Barad through concepts like apparatus, agential realism, agential cut and difference to dissect the interactions of matter with the human/inhuman and the inherent multiplicity of e-motions involved in each emotive scenario.